Perceptions on Diversity in Cardiology: A Survey of Cardiology Fellowship Training Program Directors - Anna Lisa Crowley; Julie Damp; Melanie S. Sulistio; Kathryn Berlacher; Donna M. Polk; Robert A. Hong; Gaby Weissman; Dorothy Jackson; Chittur A. Sivaram; James A. Arrighi; Andrew M. Kates; Claire S. Duvernoy; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background The lack of diversity in the cardiovascular physician workforce is thought to be an important driver of racial and sex disparities in cardiac care. Cardiology fellowship program directors play a critical role in shaping the cardiology workforce. Methods and Results To assess program directors’ perceptions about diversity and barriers to enhancing diversity, the authors conducted a survey of 513 fellowship program directors or associate directors from 193 unique adult cardiology fellowship training programs. The response rate was 21% of all individuals (110/513) representing 57% of US general adult cardiology training programs (110/193). While 69% of respondents endorsed the belief that diversity is a driver of excellence in health care, only 26% could quote 1 to 2 references to support this statement. Sixty‐three percent of respondents agreed that “our program is diverse already so diversity does not need to be increased.” Only 6% of respondents listed diversity as a top 3 priority when creating the cardiovascular fellowship rank list. Conclusions These findings suggest that while program directors generally believe that diversity enhances quality, they are less familiar with the literature that supports that contention and they may not share a unified definition of "diversity." This may result in diversity enhancement having a low priority. The authors propose several strategies to engage fellowship training program directors in efforts to diversify cardiology fellowship training programs.